Antenatal corticosteroid administration before elective caesarean section at term to prevent neonatal respiratory morbidity: a randomized controlled trial. (April 2016) - Nada, A.M.; Shafeek, M.M.; El Maraghy, M.A.; Nageeb, A.H.; Salah El Din, A.S.; Awad, M.H.
Abstract: Objective: To assess the effect of prophylactic corticosteroid administration before elective caesarean section at term (between 38 and 38 +6 weeks) in reducing neonatal respiratory morbidity and admission to a neonatal intensive care unit (NICU) with respiratory complications. Methods: Women in this study ( n = 1290) were randomized into two groups: the dexamethasone group ( n = 645) and the control group ( n = 645). Women in the dexamethasone group received three doses of intramuscular dexamethasone 8 mg, 12 h apart, 48 h before caesarean section. Women in the control group received intramuscular saline as a placebo in the same dosage as the dexamethasone group. Primary outcome: Comparison of NICU admission rates and the occurrence of neonatal respiratory morbidity between the two groups. Results: The NICU admission rate for respiratory morbidity was significantly lower in the dexamethasone group compared with the control group [10/616 (1.6%) vs 24 (3.9%), respectively; p = 0.014]. Antenatal administration of dexamethasone was significantly associated with almost 2.5-fold reduction in the risk of NICU admission for respiratory morbidity (relative risk 0.41, 95% confidence interval 0.2–0.86; number needed to treat ≅43). Conclusion: Antenatal corticosteroids reduce the incidence of NICU admission with respiratory morbidity after elective caesarean section at term.